Morphometric Analysis of Heart Development in Prenatal and Postnatal Goats (Capra hircus) - Raj, Gayatri; Taluja, J. S.; Vaish, Rakhi; Singh, Nripendra; Lade, Diksha; Tekam, Shashi; Bharti, Shashi; Jadav, Kajal Kumar (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted at the Department of Veterinary Anatomy, College of Veterinary Science and Animal Husbandry, Nanaji Deshmukh Veterinary Science University, Jabalpur, Madhya Pradesh, India, from January to June, 2020. It involved the hearts of 18 prenatal and 12 postnatal normal, healthy goats (Capra hircus). The heart was located in the ventral part of the thoracic cavity, within the middle mediastinal space, enclosed by the pericardium. In groups I and II, the heart appeared oval, while in groups III, IV and V, it assumed a flattened cone shape, reflecting progressive maturation. The heart weight relative to body weight was highest in group I and lowest in group V, indicating a gradual reduction in relative heart mass with age. A significant positive correlation was found between body weight and both heart weight and volume, with heart volume increasing consistently across all groups. The cranial border of the heart was longer than the caudal, while the coronary fat increased progressively from group I to group V, contributing to the functional efficiency of the heart. The heart’s transverse diameter exceeded the sagittal in all groups, reflecting lateral growth, while the left ventricular wall was significantly thicker than the right ventricular wall and the interventricular septum, a structural adaptation to higher pressure loads in systemic circulation. These findings provide valuable insight into the anatomical development and physiological adaptations of the heart across prenatal and postnatal stages in goats, contributing to a better understanding of cardiovascular growth patterns in this species.